Diagnóstico situacional de la nutrición infantil como política pública para asegurar el desarrollo integral de los niños que asisten al CIBV Caritas Alegres, de la ciudadela La Salud, parroquia 7 de Octubre de la ciudad de Quevedo, AÑO 2015 - Coello Guerra, Maritza Amparo (2015)
Research was conducted in order to perform a "Situational Diagnosis of Child Nutrition and Public Policy to ensure the Integral Development of children attending the Children's Center of Good Living CIBV Happy Faces, Health Citadel, parish October 7 City Quevedo, 2015 ", addressed to evaluate the diagnostic and situations that children face the need of customers. With the analysis it could meet the needs of the CIBV children need when evaluating them. This project aims to encourage and increase teaching and health care practices aimed at children who have children in assessing their medical diagnosis. It should be noted that in the Children's Center of Good Living CIBV many q1ue not lead him proper control children attending, stressing the low development of their skills. It must be taken into account to assess the situational analysis of children in the Children's Center of Good Living CIBV help gain a broad understanding of what they have weaknesses are, so either way you will find the solution, which will help to enable children to have adequate psychomotor development. However it noted that parents of children attending the Children's Center of Good Living CIBV must be aware that they must have adequate food for proper mental and emotional development